A new record of the genus Ecdelphax (Hemiptera: Auchenorrhyncha: Delphacidae) from the Korean Peninsula with a key to the species - Jaekook Park; Sunghoon Jung (Journal of Asia-Pacific Biodiversity, 2023)
The delphacid species, Ecdelphax tortilis (Kouh, 1982), is recorded from the Korean Peninsula for the first time. The morphological information such as diagnosis and redescription of male habitus and genitalia are presented with photographs, and a key to the species of genus Ecdelphax is provided.